The Livelihood Status of Career Woman in Indonesia: Revitalization of Tanqih al-Manat in Legal Reasoning - Alimuddin, Harwis; Husain, Muhammad Zakir; Abubakar, Alyasa’ (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2023)
This research discusses the livelihood status of career women in view of Islamic law and it’s urgency in Indonesia, the epistemology of tanqih al-manat in legal reasoning, and how the application of tanqih al-manat in obligation of career woman livelihood. This research uses a qualitative approach in explaining, describing and analyzing the data and find out the results of the research. The data collection technique used is a literature study. The results of this research identify that being a career woman has become an urgent need in Indonesia, because if only men have careers it will cause an imbalance between the average income and a decent standard of living. The women have the right to work like men as long as the work requires it or she herself needs the work and the work is carried out with respect and obey the religious principles and goals. Tanqih al-manat is a method of filtering the right ‘illat from various possible properties. Through the filtering process of ‘illat, it was found that the proper ‘illat from the texts of the obligation to support livelihood is the husband's control and detention in the house so that she is unable to live independently. Therefore, this research concludes that career women do not have to be supported in livelihood by their husbands, because they are no longer confined to their homes and they are able to live independently.